Effectiveness of Music Therapy on Anxiety Levels and Sleep Quality in Cancer Patients: A Systematic Review - Sitorus, Kristiani; Novieastari, Enie; Gayatri, Dewi; Nuraini, Tuti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cancer is a major global cause of death Cancer patients have a great sense of anxiety about their illness, which has an impact on their sleep quality. Music therapy intervention is one of the non-pharmacological therapies that can be given to cancer patients. It is important to identify the effectiveness of music therapy in reducing anxiety and improving sleep quality in cancer patients. Method: Journals and articles were searched using five databases ProQuest, EBSCOHost, Pubmed, ScienceDirect, and Sage Journal. The author selected several relevant journals and articles from 2010 to 2023. The results of the search of 11 articles found that music therapy interventions proved effective in reducing the stress levels of cancer patients. Music therapy can also improve the sleep quality of cancer patients. Music therapy is effective in reducing anxiety and improving the quality of sleep of cancer patients.